ANALISIS YURIDIS SISTEM PELAYANAN KUNJUNGAN TERHADAP NARAPIDANA DI LEMBAGA PEMASYARAKATAN PEREMPUAN KLAS IIA MALANG - CHRISTIN ARIYANTI ARIYANTI (Fakultas Hukum Universitas Islam Malang, 2020)
Visiting service is a form of prisoners’ rights fulfilling to keep contact with family or certain people. Visit policy is an important factor that involves conditions and procedures for conducting such visits, officers that serve the visits and other matters related to visiting service system. Policy regarding prisoners visiting are different between one correctional institution and the others.